HASIL TANGKAPAN UTAMA DAN HASIL TANGKAPAN SAMPINGAN (BYCATCH) DARI PERIKANAN DEMERSAL TRAWL SKALA KECIL DI PERAIRAN UTARA JAWA BARAT - Ronny I. Wahju; M. Fedi A. Sondita; Sugeng H. Wisudo; John Haluan (Institut Pertanian Bogor, 2008)
The total catch from small scale demersal trawl fisheries is categorised into target catch and the bycatch. The target catch were identified during the research consists of 6 species which comprises of bago (Penaeus semisulcatus), jerbung (Penaeus merguiensis), kipas (Scylaroides squamosus), krosok (Parapenaeopsis sculptilis), ronggeng (Harpiosquilla rhapidae) and windu (Penaeus monodon) with the total catch of 271,59 kg (25,41%). The bycatch which is categorised as economic highly valuable consists of 4 species such as (Loligo sp) , kepiting (Scylla serrata), rajungan (Portunus sp) and sotong (Sepia sp) with the total catch of 154,97 kg (14,50%). Then the bycatch which low economic valuable consists of 30 species 642,27 kg (60,10%), from the total catch of 1068,83 kg. The morfology of fish were dominated by compress fish with the standard length range between 7 to 20 cm and width range between 0,2 to 2,3 cm.